The process of nurses' role negotiation in general practice: A grounded theory study. - Hewitt SL; Mills JE; Hoare KJ; Sheridan NF (John Wiley and Sons Ltd, 2023)
AIM: To explain the process by which nurses' roles are negotiated in general practice. BACKGROUND: Primary care nurses do important work within a social model of health to meet the needs of the populations they serve. Latterly, in the face of increased demand and workforce shortages, they are also taking on more medical responsibilities through task-shifting. Despite the increased complexity of their professional role, little is known about the processes by which it is negotiated. DESIGN: Constructivist grounded theory. METHODS: Semi-structured interviews were conducted with 22 participants from 17 New Zealand general practices between December 2020 and January 2022. Due to COVID-19, 11 interviews were via Zoom™. Concurrent data generation and analysis, using the constant comparative method and common grounded theory methods, identified the participants' main concern and led to the construction of a substantive explanatory theory around a core category. RESULTS: The substantive explanatory theory of creating place proposes that the negotiation of nurse roles within New Zealand general practice is a three-stage process involving occupying space, positioning to do differently and leveraging opportunity. Nurses and others act and interact in these stages, in accordance with their conceptualizations of need-responsive nursing practice, towards the outcome defining place. Defining place conceptualizes an accommodation between the values beliefs and expectations of individuals and pre-existing organizational norms, in which individual and group-normative concepts of need-responsive nursing practice are themselves developed. CONCLUSION: The theory of creating place provides new insights into the process of nurses' role negotiation in general practice. Findings support strategies to enable nurses, employers and health system managers to better negotiate professional roles to meet the needs of the populations they serve, while making optimum use of nursing skills and competencies. IMPLICATIONS FOR THE PROFESSION AND/OR PATIENT CARE: Findings can inform nurses to better negotiate the complexities of the primary care environment, balancing systemic exigencies with the health needs of populations. IMPACT: What Problem Did the Study Address? In the face of health inequity, general practice nurses in New Zealand, as elsewhere, are key to meeting complex primary health needs. There is an evidence gap regarding the processes by which nurses' roles are negotiated within provider organizations. A deeper understanding of such processes may enable better use of nursing skills to address unmet health need. What Were the Main Findings? Nurses' roles in New Zealand general practice are determined through goal-driven negotiation in accordance with individual concepts of need-responsive nursing practice. Individuals progress from occupying workspaces defined by the care-philosophies of others to defining workplaces that incorporate their own professional beliefs, values and expectations. Negotiation is conditional upon access to role models, scheduled dialogue with mentors and decision-makers, and support for safe practice. Strong clinical and organizational governance and individuals' own positive personal self-efficacy are enablers of effective negotiation. Where and on Whom Will the Research Have Impact? The theory of Creating Space can inform organizational and individual efforts to advance the roles of general practice nurses to meet the health needs of their communities. General practice organizations can provide safe, supported environments for effective negotiation; primary care leaders can promote strong governance and develop individuals' sense of self-efficacy by involving them in key decisions. Nurses themselves can use the theory as a framework to support critical reflection on how to engage in active negotiation of their professional roles. REPORTING METHOD: The authors adhered to relevant EQUATOR guidelines using the COREQ reporting method. PATIENT OR PUBLIC CONTRIBUTION: Researchers and participants currently working in general practice were involved in the development of this study. By the process of theoretical sampling and constant comparison, participants' comments helped to shape the study design. WHAT DOES THIS PAPER CONTRIBUTE TO THE WIDER GLOBAL CLINICAL COMMUNITY?: An understanding of the processes by which health professionals negotiate their roles is important to support them to meet the challenges of increased complexity across all health sectors globally.
Keywords: general practice; grounded theory; negotiation; nurses; nursing; primary care; primary health care; role; Humans; Negotiating; Nurse's Role; Grounded Theory; General Practice; Workplace; Nurses